An examination of the quality of infrastructure provided in South Africa's industrial development zone - Mbambo, Dumisani Manqoba (GSB: Faculty, 2016)
A number of developing countries, particularly those in Asia, have been successful in using Special Economic Zones (SEZ) to attract Foreign Direct Investment (FDI) in export oriented manufacturing. The zones attract FDI by offering infrastructure and a hassle free business environment for investors. Most African countries that have introduced SEZs within their territories have failed to replicate the success enjoyed by a number of Asian countries. In 2000, South Africa introduced Industrial Development Zones (IDZs), another form of SEZs. The Department of Trade and Industry (DTI) defines IDZs as purpose-built industrial estates that leverage FDI in value-added and export-oriented manufacturing and services. Like other African countries, South Africa's IDZs have failed to live up to expectations. The South African zones continue to rely on Government for their current and capital expenditure. In 2006, the Government initiated a review of the IDZ Programme. The review mainly attributed the failure of the IDZ Programme to poor governance and made little reference to the infrastructure provided by the zones. In an effort to get a more comprehensive picture of the IDZs, this study investigates the quality of infrastructure within the zones. The major findings of this study have indicated that power and electricity remain a major concern in both the Coega Industrial Development Zone (CIDZ) and the East London Industrial Development Zone (ELIDZ) to zone authorities and enterprises. The two zones cannot accommodate electricity intensive operations and have resorted to focusing on enterprises that consume less electricity. It was also established that the communication infrastructure such as the cellular phone signal and internet connectivity are also a major concern within both the CIDZ and ELIDZ. This study also found that the ELIDZ does not have a deep water port to handle bulk cargo ships and that both the ELIDZ and the CIDZ do not have an efficient transportation network linking IDZ enterprises to the rest of the economy.